The Functions of Conversational Implicature in “Doctor Strange in Multiverse of Madness” 2022 - Yanika Efizahane; Afriana Afriana (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this research is to find the functions of conversational implicature in Doctor Strange in the Multiverse of Madness movie based on Grice's theory by using Cooperative Principle as a guidance. Conversational implicature is how the same sentence can be understood to have two opposite meanings even though both are conveyed explicitly. Cooperative Principles are often interpreted as general guidelines that cover conversational interactions. This research uses a qualitative descriptive method to analyze the data proposed by Sudaryanto 2015 namely the observational method. Researchers collected with are several steps taken by the researcher, first the researcher watched the movie and transcribed the conversation, the second researcher checked the utterance containing the implicature, the third researcher analyzed the highlighted data. Based on the research findings, the most dominant maxim violations that occur in this movie are relation maxim with 10 data, quality maxim violation with 6 data, quantity maxim violation with 2 data, then maxim of manner violation with 2 data.